Improving Metabolic Health Through Precision Dietetics in Mice. Issue 1 (1st January 2018) - Barrington, William T; Wulfridge, Phillip; Wells, Ann E; Rojas, Carolina Mantilla; Howe, Selene Y F; Perry, Amie; Hua, Kunjie; Pellizzon, Michael A; Hansen, Kasper D; Voy, Brynn H; Bennett, Brian J; Pomp, Daniel; et al.
Abstract: Barrington et al. examined the effect of four human diets (American, Mediterranean, Japanese, and Maasai/ketogenic) on metabolic health across four mouse... The incidence of diet-induced metabolic disease has soared over the last half-century, despite national efforts to improve health through universal dietary recommendations. Studies comparing dietary patterns of populations with health outcomes have historically provided the basis for healthy diet recommendations. However, evidence that population-level diet responses are reliable indicators of responses across individuals is lacking. This study investigated how genetic differences influence health responses to several popular diets in mice, which are similar to humans in genetic composition and the propensity to develop metabolic disease, but enable precise genetic and environmental control. We designed four human-comparable mouse diets that are representative of those eaten by historical human populations. Across four genetically distinct inbred mouse strains, we compared the American diet's impact on metabolic health to three alternative diets (Mediterranean, Japanese, and Maasai/ketogenic). Furthermore, we investigated metabolomic and epigenetic alterations associated with diet response. Health effects of the diets were highly dependent on genetic background, demonstrating that individualized diet strategies improve health outcomes in mice. If similar genetic-dependent diet responses exist in humans, then a personalized, or "precision dietetics, " approach to dietary recommendations may yield better health outcomes than the traditional one-size-fits-all approach.